Resident experiences of informal education: how often, from whom, about what and how. Issue 12 (December 2014) - Varpio, Lara; Bidlake, Erin; Casimiro, Lynn; Hall, Pippa; Kuziemsky, Craig; Brajtman, Susan; Humphrey‐Murto, Susan
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at "www.mededuc.com discuss"